Electronic resource management in libraries : research and practice - Yu, Holly; Breivold, Scott (Hershey, PA : Information Science Reference, 2008)
This book provides comprehensive coverage of the issues, methods, theories, and challenges connected with the provision of electronic resources in libraries, with emphasis on strategic planning, operational guidelines, and practices. Its primary focus is management practices of the life-cycle of commercially acquired electronic resources from selection and ordering to cataloging, Web presentation, user support, usage evaluation, and more"--Provided by publisher.
History of electronic resources / Dalene Hawthorne -- Strategic planning for electronic resource management / Melissa Holmberg, Bobby Bothmann -- Electronic usage statistics / Pat Hults -- Selecting, acquiring, and renewing electronic resources / Smita Joshipura -- Sharing the albatross of e-resources management workflow / Jodi Poe ... [et al.] -- Process mapping for electronic resources : a lesson from business models / Marianne Afifi -- Evolving roles for electronic resource librarians / Debra Engel, Sarah Robbins -- Evolution of license content / Trisha L. Davis, Celeste Feather -- Copyright implications for electronic resources / Aline Soules, Donna L. Ferullo -- Tactics and terms in the negotiation of electronic resource licenses / Kincaid C. Brown -- Working with database and e-journal vendors to ensure quality for end users / Heather Christenson, Sherry Willhite -- One-stop shopping for journal holdings / Janet Crum -- Beyond openURL : technologies for linking library resources / George Boston, Randle J. Gedeon -- Authentication and access management of electronic resources / Juan Carlos Rodriguez, Bin Zhang -- Using consistent naming conventions for library electronic resources / Diana Kichuk -- Standards, the structural underpinnings of electronic resource management systems / Ted Koppel -- Challenges and potentials of electronic resource management / Yvonne Wei Zhang -- Panorama of electronic resource management systems / Margaret Hogarth, Viki Bloom -- Impact of locally developed electronic resource management systems / Marie R. Kennedy -- Future of electronic resource management systems : inside and out / Ted Fons -- In the eye of the storm : ERM systems guiding libraries$1 (Bfuture / s Ted Koppel.
"Premier reference source"--Cover.
Includes bibliographical references (p. 383-408) and index.
1
Keywords: Libraries -- Special collections -- Electronic information resources; Electronic information resources -- Management